PENYIDIKAN TINDAK PIDANA PERBANKAN OLEH PENYIDIK DIREKTORAT RESERSE KRIMINAL KHUSUS DI WILAYAH HUKUM KEPOLISIAN DAERAH RIAU - Roki Oktavianaldi; Dessy Artina; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
In the Banking system in Indonesia there are many abuse of authority and deviation in running the activities of Banking in various ways and modes that aims to enrich themselves and a certain group of people, resulting in many occurrence of forms of violations and forms of crime in banking activities. From the increasing impact of banking crime, it is necessary for the role of Police as law enforcement in conducting investigation and investigation process on handling banking crime to provide legal certainty and protect banking activities. From the results of observation on the location of research in the investigation process by Investigator Directorate of Special Criminal Investigation Polda Riau there is handling of banking case long enough run but until now still experiencing obstacles. thus hindering the settlement of a case and an enforcement in Banking activities.From various observations and data collection and information in the form of interviews with related parties to the object of research, it can be formulated issues such as: (1) How to Investigate Bank Crime by Investigator Directorate of Special Criminal Investigation in Riau Province Police Territory; and (2) What are the obstacles of Investigation of Banking Crime by Investigator of Special Criminal Investigation Directorate in Riau Province Police Territory.Handling of banking crime by investigator based on Standart Operational Procedure (SOP), and clarified The stages related to the implementation of law enforcement professional and procedural in jurisdiction Ditreskrimsus Polda Riau, with several stages ranging from acceptance of complaints from the community, the process of investigation, the process of investigation to the final stage that is by delegating the case file declared completeto the Public Prosecution Serviceat the Riau High Prosecutor's Office. Obstacles Investigators in the investigation of Banking crime are at the time of collection of documents or important letters from the Bank, and also in the case of personnel changes where the banking crime case will be replaced by a new investigator so it is necessary to coordinate between the old investigator and the new one so as to require a long time in the settlement of a case, this obstacle is sought by the investigator as much as possible resolved to provide legal certainty against the investigation of Banking crime.